The Effect of Accounting Understanding and Tax Provisions on Calculating, Depositing, and Reporting of Tax at Pt. Xyz - A Case Study on a Startup - Panduwinata, Vina; Sidharta, Juaniva; Simanjuntak, Ramot (Advances in Social Sciences Research Journal, 2022)
Technological developments gave a lot of influence on human life in general, from daily activities until there are several digital-based business models, known as startups. As of 2018, according to MIKTI (Indonesian: Masyarakat Industri Kreatif Teknologi Informasi, or Information Technology Creative Industry Society) database, there were 992 startups in Indonesia. Startup company tax is an obligation that must be paid on income received or transactions related to withholding PPh (Indonesian: Pajak Penghasilan, or Income Tax) made by startup companies and requires special tax treatment in order to develop their business. The factor of understanding tax accounting provides a significant contribution to the compliance of corporate taxpayers in fulfilling income tax obligations. The research in this journal aims to gain knowledge of the extent of understanding of accounting and tax provisions in depositing and reporting taxation at one of the startups in Greater Jakarta.